Comparative analysis of load profile between small-sided games and official matches in youth soccer players - Gómez-Carmona, C. D.; Gamonales, J. M.; Pino-Ortega, J.; Ibanez, S. J. (Sports, 2018)
The purposes of the present study are: (a) to characterize the external (eTL) and internal load (iTL) of official matches and small-sided games (SSGs) in relation to their objective, (b) to compare demands between SSG, and (c) to analyze the SSG requirements in relation to official matches during a one-month competition period. Twenty under-18 national-level soccer players were recorded using WIMUTM inertial devices (RealTrack Systems, Almeria, Spain) during four official matches and 12 training sessions where four SSGs with different objectives were performed: (SSG1) keeping the ball; (SSG2) keeping the ball and progressing; (SSG3) keeping the ball, progressing and ending in mini-goals; and (SSG4) keeping the ball, progressing and ending in an official goal with a goalkeeper. Statistical analysis included Kruskall-Wallis` H and Mann-Whitney`s U with Cohen`s d effect size. The SSGs presented walking and jogging intensity movements (0.7-7 to 7-14 km/h), with a 5-to-8 %HIA (high intensity activity, >16 km/h), where low intensity accelerations, decelerations and impacts were predominant (1-2.5 m/s2; 5-7 G), and %HRMAX (maximum heart rate percentage) was between 70-90%. Only SSG4 presented similar demands to competition, finding differences between SSGs (p < 0.05; d = 1.40 - 0.36). In conclusion, the objective of the SSGs directly influenced the demands on the players in training sessions. For this reason, it is important to monitor demands for designing specific training sessions